A study on the perception towards quality training and development at AKMAL Sabah / Leonie Joseph - Joseph, Leonie (2011)
The main objective of this study is to examine the perception of the trainee on the quality of the training program organized by AKMAL Sabah. This paper identifying five factors (areas) which consist of the training facilities, seniority, level of education, division of job and content of the training program. Operational measures of these factors are developed using data collected from 198 respondents that attending for the four (4) courses which conducted at the AKMAL Sabah. The overall result of the study showed that there is significant positive relationship between the perception towards the quality training, facilities and also the content of the training program. This indicates that the participants who come to the training program have a very optimist perception towards the training program conducted by the AKMAL Sabah. However, there has been no systematic attempt to organize and synthesize the various prescriptions offered, nor have measures of organizational quality training been proposed for areas such as top management leadership, training and employee involvement.